Fruit growth, final size and yield in 'Valencia' orange (Citrus sinensis L. Osb.) with 2,4-dichlorophenoxy propionic acid sprays - Ferenczi, A.; Gambetta, M.; Franco, J.; Arbiza, H.; Gravina, A. (Agrociencia Uruguay, 1999)
Direct effect of the 2,4- dichlorophenoxy propionic acid (2,4-DP) applied at the end of physiological drop to improve fruit size in 'Valencia' orange adult plants, has been studied for two years. Fruit growth was not affected by the 2,4-DP application since significant differences in daily fruit growth rate and in the fruit growth curve between treated and untreated fruit were not found. In Paysandú, in both years, neither fruit number, nor fruit size (expressed in weight or diameter) and yield per tree, were significantly modified with the 2,4-DP application. The average values obtained were 712 fruit.tree-1, 193 g, 71.2 mm and 137 Kg.tree-1, respectively. In Río Negro, fruit number (1875 vsl 711) and yield per tree (258 Kg.tree-1 vs 234 Kg.tree-1) diminished significantly in treated trees, whereas final fruit size remained unchanged (average of 138 g, 65.2 mm). Asignificant reduction in fruit number with the application of 2,4-DP, was found only in Río Negro in fruit smaller than 64mm in diameter. An inverse correlation was obtained between fruit number per tree and average fruit weight (r = -0.79) considering the experiments altogether. The results of this report do not allow us to confirm a positive response in fruit growth and fruit final size in 'Valencia' orange, with the 2,4-DP application at the end of June drop under the productive conditions studied.